DEVELOPMENT OF CALCULATION METHODOLOGY OF MATERIAL MELTING PROCESSES ON THE BASIS OF INSTANTANEOUS REGULAR MODE - V. M. Olshansky; N. P. Svinolobov; V. I. Timoshpolsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
While using the method of instantaneous regular mode an approximate solution of the task concerning melting of bodies with a simple shape - a plate, a cylinder and a sphere - has been obtained. At the same time cases of melting of «thermally thin» and «thermally massive» bodies under condition of instantaneous removal of melt and retaining the melt on the surface of the body have been investigated.